La expresión corporal, como medio de comunicación educacional - Guerrero Laurido, Hugo Enrique (2017)
The body language is an important content as a means of communication with their environment. That is, it is a multidisciplinary content of origin, we must define what the concept we left and streams or pillars that support our work in education. We will also define the goals or objectives we want to achieve through the expressive capabilities, sequencing them and showing some didactic concepts for development.The conceptof bodily expression has been analyzed from different aspects or areas, as Ortiz says in his text on body language (2002), although this term is ambiguous and versatile, we approached from the educational field, more as an educational tool; yet, never letting go of what conduct or representation communicates all.Ortiz (2002: 25) is an approach to the concept of body language from numerous contributions by various authors. From these states that in the field of physical education and any other material body language should contribute to the development of the individual enhancing the knowledge and development of body language through different techniques favorable "reveal or externalize the innermost and depth of each individual through the body and movement, ie, expressing "reinforce the use of the body and movement as media, ie, communicate and analyze the aesthetic and artistic value of the body".